Role of biofilms in antimicrobial resistance of the bacterial bovine respiratory disease complex - Andrés-Lasheras, Sara; Zaheer, Rahat; Jelinski, Murray; McAllister, Tim A. (Frontiers in Veterinary Science, 2024)
An increase in chronic, non-responsive bovine respiratory disease (BRD) infections in North American feedlot cattle is observed each fall, a time when cattle are administered multiple antimicrobial treatments for BRD. A number of factors are responsible for BRD antimicrobial treatment failure, with formation of biofilms possibly being one. It is widely accepted that biofilms play a role in chronic infections in humans and it has been hypothesized that they are the default lifestyle of most bacteria. However, research on bacterial biofilms associated with livestock is scarce and significant knowledge gaps exist in our understanding of their role in AMR of the bacterial BRD complex. The four main bacterial species of the BRD complex, Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis are able to form biofilms in vitro and there is evidence that at least H. somni retains this ability in vivo. However, there is a need to elucidate whether their biofilm-forming ability contributes to pathogenicity and antimicrobial treatment failure of BRD. Overall, a better understanding of the possible role of BRD bacterial biofilms in clinical disease and AMR could assist in the prevention and management of respiratory infections in feedlot cattle. We review and discuss the current knowledge of BRD bacteria biofilm biology, study methodologies, and their possible relationship to AMR.